Materials And Education Method For Preparation Of Childbirth And Postnatal Period In Antenatal Classes: A Scoping Review - Fatimatasari Fatimatasari; Mohammad Hakimi; Luluk Rosida (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Education in preparation for childbirth and the postnatal period through antenatal classes has long been known and was first aimed at reducing anxiety and labor pain. Recently, education for preparation for childbirth and the postnatal period through antenatal classes is increasingly being promoted and its goals are also growing. However, there is no clear information about what forms of education for preparation for labor and the postnatal period in the antenatal class have been researched by experts. The study aimed to systematically map the research conducted in this area, as well as to identify existing gaps in knowledge. Scoping Review with reference to PRISMA Extension for Scoping Reviews (PRISMA-ScR) by using three databases for article searches, which are MEDLINE, ProQuest and EBSCO. We found 18 relevant research articles which published 16 different education programs for labor preparation and postnatal period. The educational material presented includes preparation for childbirth, the postnatal period and decision making. The delivery methods used included the start time of education, the number of meeting sessions, the duration of the meeting, the use of a special room for, the number of members per session, the participation of couples in sessions, learning methods, routine exercises in class, implementation of exercises at home, educators or facilitators who convey, the implementation of visits to the delivery room, and the use of supporting information technology. Education preparation for labor and the postnatal period in the literature uses a variety of delivery methods and material topics. Existing research measures different outcomes and shows quite diverse effectiveness on labor and postnatal periods.The next researcher is expected to conduct research on education programs for childbirth preparation and the postnatal period by referring to the latest evidence based and using RCT research methods and a large sample size and multi-center.